Factors and relationships influencing self-regulated learning among ICT students in Australian Universities - Balapumi, Rohini (Curtin University, 2015)
This study examined the factors influencing ICT students’ practices and teaching staff facilitation of self-regulated learning (SRL). Data from students and staff in 34 universities in Australia were analysed using the structural equation modeling (SEM-PLS) approach. Teaching and learning goals and beliefs, Self-Regulated Learning awareness and knowledge and university support systems were found to significantly influences student SRL practices and staff SRL facilitation. These findings inform university academic leaders in providing the necessary guide and support for teaching staff to facilitate and provide opportunities for students to practice self-regulated learning in university education.